On the composition of microtwins in a single crystal nickel-based superalloy - Barba, D; Pedrazzini, S; Vilalta Clemente, A; Wilkinson, A; Moody, M; Bagot, P; Jerusalem, A; Reed, R (Elsevier, 2016)
Correlative analysis is performed using atom probe tomography and high resolution transmission Kikuchi diffraction techniques on microtwins of ∼10 nm thickness, in a ⟨011⟩-orientated single crystal superalloy crept at 800 °C and 650 MPa. Composition profiles across the microtwins and microtwin-parent boundaries are presented. Enrichment of microtwin-parent interfaces by approximately 2 at.% Cr and 1 at.% Co within the γ′-phase is found; no compositional variations of other elements – Ta, Nb, Mo, W – are detected. Our results provide unique insights into the mechanism of microtwin formation and the likely influence of alloy composition on deformation kinetics.